Authentic Dasein and the anxious uncanny - Seifeldin Khalifa, Hend Diaa Diaa (AUC Knowledge Fountain, 2012)
The philosophical reader cannot help but notice that some of the major assertions of Immanuel Kant and Martin Heidegger are thematically intertwined. Perhaps even more clearly, the viewer who approaches the work of Edvard Munch with a philosophical frame of mind will discover how the thoughts of Kant and Heidegger often illuminate key aspects of his paintings. Authentic Dasein and the Anxious Uncanny strives to analyze the main works of Edvard Munch, the father of Expressionism. This thesis uses Heidegger's concepts of anxiety and being-towards-death, as well as Kant's notion of the Sublime as laced with anxiety, to re-examine nineteen of the artist's masterpieces. The first chapter explores the relationship between Kant and Munch, while the second focuses on artist's works through the philosophy of Heidegger. The third and concluding chapter brings together Kant and Heidegger through a series of paintings to demonstrate how Munch's achievement can be interpreted philosophically.